Anticipatory Grief Among Close Relatives of Persons With Dementia in Comparison With Close Relatives of Patients With Cancer. (February 2013) - Johansson, Åsa K.; Sundh, Valter; Wijk, Helle; Grimby, Agneta
Close relatives of persons with dementia self-reported reactions on the Anticipatory Grief Scale (AGS), were observed by nurses (Study I), and compared with relatives of cancer patients in a study using the same methodology (Study II). Study I showed an overall stressful situation including feelings of missing and longing, inability to accept the terminal fact, preoccupation with the ill, tearfulness, sleeping problems, anger, loneliness, and a need to talk. The ability to cope was, however, reported high. Self-assessments and nurses' observations did not always converge, e.g. for the acceptance of the illness. The reactions of the relatives in the dementia and the cancer groups showed more similarities than dissimilarities. However, the higher number of responding spouses in the cancer group may have influenced the outcome.